An investigation into the organisational culture at an academically successful secondary school in Namibia - Awarab, Erwin Ronald (Rhodes University, Faculty of Education, Department of Education, 2010)
The appreciation by leadership of the culture of an organisation plays an important role in the success of that organisation. Leadership and organisation culture are an inextricable part of the life of an organisation. The shared assumptions and beliefs of the individual within an organisation shape its culture. My study investigates the aspects of school culture and, further, looks at its link to the success of an organisation, and at the leadership style that influences such an organisation. My research, conducted in the interpretive paradigm, is a case study which was carried out at a public secondary school in the capital city of Windhoek, in Namibia. Since the school was built during South African rule, it was intended mainly for white children. Since independence, it has undergone transformation and is currently integrated, accommodating learners from different cultural backgrounds. It is a successful school, with a good reputation for its discipline and academic excellence. I chose this school deliberately, for those reasons. My findings are that there are aspects of culture which maintain its creation and perpetuate the existence of a particular culture at the school. This school's culture is embedded within the Christian faith, and there are deliberate rituals and ceremonies put in place to enhance the creation and maintenance of the values that inform its culture, and the school leadership, management, teachers and student council members have a central role in this regard. My study shows that the creation, understanding and appreciation of beliefs and values of the individual within the organisation enable the consequent creation of the shared vision and values that ultimately lead to the foundation and maintenance of a strong culture.
Keywords: Corporate culture -- Namibia -- Case studies; Organizational behavior -- Namibia -- Case studies; School management and organization -- Namibia -- Case studies; Educational leadership -- Namibia -- Case studies; Education, Secondary -- Namibia -- Case studies; Educational change -- Namibia -- Case studies